Rethinking Islamic Education: Incorporating Values of Religious Moderation in the Modern Era - Ahmad Farchan Anggitama; Irfan Afandi; Al Muftiyah (Journal of Educational Management Research, 2026)
This study aims to describe the insertion of religious moderation values in Islamic Religious Education (IRE) learning and to examine how these values are integrated, internalized, and practiced within the educational process. Employing a qualitative approach with a single-case study design, data were collected through semi-structured interviews, moderate participant observation, and document analysis involving IRE teachers, students, school leaders, guidance and counseling teachers, and homeroom teachers selected purposively. Data were analyzed using thematic analysis through transcription, coding, categorization, and theme development. The findings reveal four main patterns of religious moderation insertion: the integration of moderation values into IRE lesson planning, the implementation of dialogic, reflective, and contextual learning strategies, the internalization of moderation values through school culture, and students’ experiences in interpreting and practicing religious moderation in their daily lives. These findings indicate that religious moderation is not merely presented as normative content but functions as a socio-pedagogical practice shaped by the interaction of curriculum, teachers, school culture, and students’ lived experiences. The study implies the need to strengthen instructional planning, attitude assessment, and collaborative school programs to foster an inclusive, tolerant, non-violent, and contextually responsive Islamic education ecosystem.